Development of a Smart Cooling and Fertigation System for Strawberry Cultivation in Tropical Lowland Greenhouses - Mohd Zain, Ahmad Zairi; Ali, Nor Sukor; Tasuki, Norazleen; Ahmad, Nurulain; Jaafar, Mohd Zulhilmi (Emerging Advances in Integrated Technology, 2025)
Strawberry cultivation in tropical lowland regions faces major challenges due to excessive heat, high humidity, and poor root zone temperature regulation, often leading to low fruit quality and inconsistent yields. This project aims to address these limitations by integrating environmental optimization with smart agricultural technology tailored for tropical greenhouse applications. The main objective is to develop a sustainable, IoT-enabled fertigation and microclimate control system for strawberry cultivation in lowland Malaysia, focusing on improving yield, fruit sweetness, and plant resilience. A comprehensive review was conducted on critical environmental parameters like temperature, humidity, light intensity, CO? levels, and electrical conductivity combined with a study of recent innovations in precision agriculture. Based on this review, a prototype system is proposed featuring solar-powered chillers, automated misting, root zone cooling, and fertigation component controlled by ESP32 microcontrollers. The system includes real-time sensor feedback and wireless control to maintain optimal growing conditions. The proposed system will be developed at Politeknik Sultan Haji Ahmad Shah (POLISAS) and will be tested in a real-world setting at FELDA Bukit Sagu 2, a rural farming community in Kuantan. Preliminary simulations from review suggest a greenhouse temperature reduction of 4°C–6°C and improved root zone stability, aligning with recommended growth thresholds. These improvements are expected to enhance strawberry size, sweetness (Brix value), and shelf life. The novelty of this project lies in its context-specific combination of smart cooling and fertigation technologies in a modular, scalable design suitable for low-resource farming environments. It bridges academic innovation and practical agriculture, supported by sustainable energy integration and data-driven control. The project idea has gained early recognition in institutional R&D and is positioned for further collaboration with agricultural research bodies (e.g., MARDI), smart farming startups, and rural development agencies. With continued development, the system offers potential as a replicable model for tropical horticulture, supporting Malaysia’s goals for agrotechnology innovation and food security.